The impact of COVID-19 on familial Mediterranean fever: a nationwide study - DURUÖZ, MEHMET TUNCAY (SPRINGER HEIDELBERG, 2021)
The study aimed to evaluate the impact of the coronavirus disease 2019 (COVID-19) in patients with familial Mediterranean fever (FMF) and to assess the relationships between FMF characteristics and severe COVID-19 outcomes such as hospitalization. The study was planned within a national network of 21 different centers. Demographics, FMF-related clinical and genetic characteristics, and COVID-19 outcomes were obtained. A total of 822 patients with FMF (mean age of 36 years) were included in the study. Fifty-nine of them (7%) had a COVID-19 diagnosis confirmed by real-time PCR test or chest CT findings. Most FMF patients with COVID-19 (58) had mild and moderate disease activity. All patients were on colchicine treatment. However, 8 of them (13.6%) were not compliant with colchicine use and 9 of them (15.3%) were colchicine resistant. Twelve FMF patients with COVID-19 were hospitalized. There were 4 patients requiring oxygen support. COVID-19 related complications were observed in 2 patients (1 thromboembolism, 1 acute respiratory distress syndrome). Hospitalized COVID-19 patients with FMF were older than non-hospitalized patients (median ages: 51 and 31 years, respectively; p: 0.002). Other FMF-related characteristics were similar between the groups. FMF-related characteristics were not found to be associated with poor outcomes in COVID-19. Thus, FMF may not be a risk factor for poor COVID-19 outcomes.
Keywords: COVID-19; Familial Mediterranean fever; Rheumatic diseases; Colchicine; Hospitalization; Poor outcomes